Evaluating the impact of distance learning on gender-affirming healthcare competence: knowledge acquisition and satisfaction among healthcare professionals in Italy - Favazzi, Ughetta Maria; Marconi, Matteo; Carbone, Pietro; Guerrera, Debora; Ruocco, Angela; Manoli, Martina; Molinaro, Francesca; Regini, Federica Maria; Vittozzi, Andrea; Mazzaccara, Alfonso; Pierdominici, Marina (Frontiers in Public Health, 2024)
Transgender and gender diverse (TGD) individuals face significant healthcare barriers, with one of the most critical being the inadequate knowledge and skills of healthcare professionals (HCPs) in TGD health. To address this issue, we undertook a project to develop a distance learning course for all healthcare professions, encompassing a comprehensive range of topics related to TGD health issues. This study aimed to evaluate the impact of a course on gender-affirming healthcare competence, with a focus on knowledge acquisition and satisfaction levels. The hypothesis was that participating in the course would enhance the participants' knowledge on the covered topics. A distance learning course, designed for all Continuing Medical Education professions, was conducted between March and September 2023. The course was structured according to the Problem-Based Learning methodology. We implemented a pre-test vs post-test study design to evaluate the enhancement of knowledge, based on a set of Multiple Choice Questions (MCQs), and investigated users' satisfaction through the administration of a semi-structured questionnaire. We examined the pre-and post-course proportions of correct responses to questions, along with the mean score difference, categorized by learners' sex, age, and geographical area. Eventually, a Satisfaction Training Index was created. The maximum capacity was reached, with 29,998 out of 30,000 available spots filled. Of those enrolled, 18,282 HCPs successfully completed the training. Post-test results revealed an increase in correct answers across all MCQs, with overall mean score rising from 48.8 to 68.0 (p < 0.001). Stratified analysis indicated improvements across all participant categories. A higher average increase among female (19.87) compared to male enrollees (17.06) was detected (p < 0.001). Both "over 55" and "46-55" age groups showed the greatest score increases compared to "35-46" and "under 35" groups, despite no significant differences in pre-test scores. Course satisfaction was high, averaging 4.38 out of 5. Top-rated aspects included "learning new concepts" (4.49), "accessibility" (4.46), and "platform functionality" (4.46). Our research hypothesis was confirmed by the significant increase in knowledge going from pre-test to post-test and by the high level of user satisfaction. The obtained results serve as a foundation for planning additional professional education in TGD health.